Analysis of the Use of Google Meet as a Student Learning Facility in Economics Education during the Covid-19 Pandemic - Ni Luh Kardini; Anyan Anyan; Richard Andreas Palilingan; Arvida Bar; Khamaludin Khamaludin (Universitas Muhammadiyah Enrekang, 2023)
facility in economics education during the COVID-19 pandemic. This study uses qualitative and narrative research. Population in this study are Private High Schools Students in Medan City in 2022. Because the official data for Private High Schools Students in Medan City in 2022 is difficult to find, sample is taken randomly. So, sample in this study are 100 Private High Schools Students in Medan City. Data analysis technique of this research uses reading and note taking techniques. The research results show that before the COVID-19 pandemic, learning activities are carried out as usual, including Private High Schools in Medan City. Teachers and students usually complete face to face learning activities more frequently. However, since the imposition of social restrictions, school policy states that learning activities are carried out online or based on e-learning. Most schools in Indonesia utilize Google Meet application as the learning media used.